Mechanisms of cancer metastasis. (December 2022) - Castaneda, Maria; den Hollander, Petra; Kuburich, Nick A.; Rosen, Jeffrey M.; Mani, Sendurai A.
Abstract: Metastatic cancer is almost always terminal, and more than 90% of cancer deaths result from metastatic disease. Combating cancer metastasis and post-therapeutic recurrence successfully requires understanding each step of metastatic progression. This review describes the current state of knowledge of the etiology and mechanism of cancer progression from primary tumor growth to the formation of new tumors in other parts of the body. Open questions, avenues for future research, and therapeutic approaches with the potential to prevent or inhibit metastasis through personalization to each patient's mutation and/or immune profile are also highlighted.